Memória traumática resistente à extinção, comportamento sensório-motor da marcha e histofisiologia da amígdala medial : uma análise integrativa em um modelo murino - Medeiros, Filipe Mello (2016)
Suffer traumatic experiences are a risk factor for developing neuropsychiatric movement disorders. In the present study, we test the hypothesis that aversive, resistant to extinction memories could impair skilled walking performance and change neuron and glia densities as well as neuron-glia ratio in medial amygdala in male Wistar rats. Thus, we established a major trauma protocol able to induce a resistant to extinction memory followed by testing its effects on skilled walking performance and medial amygdala histophysiology. Footshocks exposure reduces skilled walking performance 3 days after the hit (P<0.0001). Additionally, the adoption of a “safety behavior” in the plus maze test was associated with worse ladder walking performance (P<0.001). Statistical trend of significance were founded for changing glia (P=0.10) and neuron-glia ratio (P=0.08) in medial amygdala as well as for their correlation with sensorimotor performance (P=0.06). Therefore, suffering traumatic experiences able to generate resistant to extinction memories could result in long-term impairment of gait control, which affects the walking ability.